POETICAL CARACTEROLOGY OF AN ANDEAN DRUNK - Ballon Aguirre, Enrique (2010)
This article is about how the poetic colonial Andean production (Pcru, XVII c.) fallswithin the Hispanic American baroque. There are rv.·o of the poems thar have been attributedro Juan del Valle and Caviedas (1645?-1698) portrays an alcoholic's whole ~elf,this allows the study of the rheroric media implied in the prosopographic constitutionof each of the poems assembled by rhis common rheme. Due ro the descriptive toolsand the semantk intetpretation that is used to compare rhe sirnilar media used on rhewestern pictorial prosopography of each (mise-en-abyme, metastability and anamorphosis)trying ro show the commut}-ity between texts and images.